Navigating regulatory challenges in molecularly tailored nanomedicine - Ajay Vikram Singh; Preeti Bhardwaj; Aditya Kumar Upadhyay; Anselmo Pagani; Jyoti Upadhyay; Jolly Bhadra; Veronica Tisato; Manali Thakur; Donato Gemmati; Rudresh Mishra; Paolo Zamboni (Exploration of BioMat-X)
Nanomedicine, a convergence of nanotechnology and medical sciences, has unleashed transformative potential in healthcare. However, harnessing the benefits of nanomedicine requires a thorough understanding of its regulatory landscape. An in-depth discussion of regulatory considerations, including molecular safety assessment, harmonization of the regulatory landscape, and shaping the future of innovation, is presented in this discourse. The molecular safety assessment entails evaluating interactions between nanoparticles and biomolecules, ensuring compatibility at the molecular level. Harmonization involves developing international standards and guidelines for a consistent regulatory approach, while shaping innovations emphasizes integrating molecular safety assessments into early stages of development. Challenges encompass the need for standardized assessment methods, balancing innovation with safety, and addressing unique features of novel molecular designs. As the nanomedicine landscape evolves, effective regulatory strategies must navigate the intricate interplay of molecules and technologies, ensuring both patient access and product safety.